Social relationships & language discourse: The influence of friendship & personality on meaning negotiation among international students - Tam, Nguyen Thi Dan (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
This study investigates the influence of friendship and personality on meaning negotiation among international students. It was conducted with three students from different countries who are studying at University of Birmingham, the United Kingdom. The qualitative method was applied, focused on a case study. Two conversations among three students with different level of acquaintances were analysed in terms of types of meaning negotiation. Through both quantitative and qualitative data analysis, the findings show that friendship and personality have the impact on meaning negotiation in terms of types, the willingness to negotiate and show emotion, the confidence to start a new point in the conversations, and the register of language during the negotiation process.